EVALUATION OF THE FORESTRY DYNAMICS IN PREMONTANE FORESTS OF SATIPO, PERU - PERALES-VARGAS, Carlos Eduardo (2023)
The study of forestry dynamics helps us to see the trends of forests in the future. In this research, forest dynamics was evaluated based on mortality and recruitment in two permanent plots located in premontane forests between 800 and 1500 masl in the province of Satipo, in the department of Junín, in the Central Forest of Peru. The Santa Teresa Primary Forest Plot (P-SPI) is located in a primary forest and recorded an initial population of 698 tree individuals, it was remeasured after an intercensal period of 5 years, registering 80 dead individuals, 77 recruits, with a final population of 695 trees and presented an annual mortality rate of 2,43% and an annual recruitment rate of 2,35%. While the Santa Teresa Late Secondary Forest Plot (P-SST) located in a late secondary forest had an initial population of 832 trees, it was remeasured after an intercensal period of 8 years, registering 152 dead individuals, 101 recruits and a final population of 781 trees, obtaining an annual mortality rate of 2,52% and an annual recruitment rate of 1,73%. The results indicate that the P-SPI forest is in dynamic equilibrium, while P-SST shows a moderate decrease in its tree density. The Euphorbiaceae, Urticaceae, Burseraceae and Moraceae families presented the highest levels of recruitment between both forests. While, the forest species Senefeldera inclinata, Vochysia venulosa, Alchornea glandulosa, Clarisia biflora and Inga ruiziana a due to their recruitment and reported uses should be considered in ecological restoration projects in the study area